Opportunities and challenges of radiofrequency ablation for substernal goiter: a case report - Han, Zhiming; Feng, Lei; Wang, Nan (Frontiers in Oncology, 2025)
Substernal goiter (SG) refers to an enlargement of the thyroid gland that extends below the sternal notch or clavicle. While most cases are benign, a few may be malignant. Surgical resection is the standard treatment for SGs that cause clinical symptoms. This case report presents a 60-year-old female SG patient with a history of thyroidectomy and congenital vascular anomalies, who developed symptoms including significant airway compression and difficulty swallowing liquids. Following a detailed imaging and pathological evaluation, ultrasound-guided radiofrequency ablation was performed at the patient’s request. The procedure was successful and led to a favorable clinical outcome. This case highlights a potential alternative treatment approach for patients with SG, particularly those for whom surgery may pose additional risks.